(untitled) (Indian Journal of Public Health Research & Development, 2021)
Background: Denture prostheses are significant interventions in oral environment for restoring lost form and function due to tooth loss. Little is known about change in microflora in removable partial denture wearers with age and time since denture delivery. Therefore, the present study was conducted to evaluate and compare the oral microbial flora pre and post insertion of removable partial denture at different time intervals and age groups. Materials and Method: A sample of 60 patients wearing removable partial denture was included in the study, 30 of age group 40-50 years (Group 1) and 30 of age group 50-60 years (Group 2).Sample of unstimulated saliva was collected from the patient’s mouth from the distal most edentulous area using three sterile cotton swabs by one investigator. Colony count and identification of microorganisms was done. Results: The difference among mean colony counts between group 1 and 2 were not statistically significant at any of the three timeintervals. A statistically significant difference in colony counts was seen between baseline, 1 month and 3 months in whole sample as well as both the age groups. Among various aerobic microorganisms, Streptococcus mitis, Diphtheroids and Candida Albicanswere the most prevailing aerobic micro organism after 3 months of denture use, while among anaerobic organisms, Prophyromonasgingivalis was the most prevalent microorganism after three months. Conclusion: A significant difference in colony count as well as colonizing microorganisms has been found in the present study. This difference according to time is an important component in the affect of removable partial denture on oral health of denture wearers. Age group was not a significant factor affecting microbial health in RPD wearers.